Chemical Composition of Vermicompost Made from Organic Wastes through the Vermicomposting and Composting with the Addition of Fish Meal and Egg Shells Flour - N Nurhidayati; Usman Ali; Indiyah Murwani (The Journal of Pure and Applied Chemistry Research, 2017)
Chemical composition of compost is an important indicator that determines the quality of compost. This study compared the chemical composition of vermicompost resulting from the process of vermicomposting alone with combined vermicomposting and composting with addition of egg shells flour and fish meal. Organic wastes used were the mixture of spent mushrooms waste, coconut husks, cow dung, vegetables residue, and leaf litter. Lumbricus rubellus was the species of earthworm used in the vermicomposting process. In the composting process, egg shells flour and fish meal are added into the vermicompost as additives materials. The results indicate that the combined vermicomposting and composting process with addition the additives materials improves the chemical composition of vermicompost compared to using vermicomposting process alone. The change of chemical composition was indicated by a decrease in C-organic content and C/N ratio by 29% and 99%, respectively, while the content of N, P, K and S increased by 52%, 67.5%, 29% and 25%, respectively due to the addition of additives material in the composting process. The largest increase of vermicompost nutrient content occurred in the Ca content by an average of up to 7-fold. While polyphenols, lignin and cellulose content of vermicompost decreased slightly. The treatment of two mixture (a) spent mushrooms waste, cow dung and vegetables residue, and (b) spent mushroom waste, cow dung, vegetables residue, and leaf litter gave the best chemical composition. However, to determine the quality, we need to test the product in a plant growth bioassay as a follow-up study.